2021
DOI: 10.3389/fpls.2021.738769
|View full text |Cite
|
Sign up to set email alerts
|

Species Distribution Models of the Spartina alterniflora Loisel in Its Origin and Invasive Country Reveal an Ecological Niche Shift

Abstract: Spartina alterniflora is a perennial herb native to the American Atlantic coast and is the dominant plant in coastal intertidal wetlands. Since its introduction to China in 1979, it has quickly spread along the coast and has caused various hazards. To control the further spread of S. alterniflora in China, we first reconstructed the history of the spread of S. alterniflora in its invasion and origin countries. We found that S. alterniflora spreads from the central coast to both sides of the coast in China, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…These ndings suggested that wetlands with high salinity and low elevation are more suitable for S. alterni ora growth. Similar ndings have also been reported by (Yuan et al, 2021), who found that the strong salt tolerance of S. alterni ora is an excellent adaptation of plants in coastal wetlands to salinity environment.…”
Section: Discussionsupporting
confidence: 90%
“…These ndings suggested that wetlands with high salinity and low elevation are more suitable for S. alterni ora growth. Similar ndings have also been reported by (Yuan et al, 2021), who found that the strong salt tolerance of S. alterni ora is an excellent adaptation of plants in coastal wetlands to salinity environment.…”
Section: Discussionsupporting
confidence: 90%
“…Q. spinosa distribution occurrence data and selected environmental variables were loaded into the MaxEnt model. The data were randomly divided: 75% of the location point data were used as a training model, with the remaining 25% used for validating the MaxEnt model [ 37 , 38 ]. By default, the maximum number of iterations was set as 10,000, the model was repeated for 10 times, and the predicted results were output in “Cloglog” format and “asc” file type [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The software ENMTools v1.4 was used to calculate the niche breadth in the geographical and environmental space of each period as the average Levins B1 (inverse concentration) and B2 (uncertainty) values of the habitat suitability map for each period (Warren et al, 2008;Levins et al, 1968). Levins B1 and B2 values range from 0 to 1, with values close to 0 representing a narrow niche breadth and values close to 1 representing a wide niche breadth (Yuan et al, 2021).…”
Section: Niche Differentiation Analysis and Priority Reserve Analysismentioning
confidence: 99%
“…The size of niche overlap reflects the similarity of plant utilization resources. Large niche overlap indicates that they have similar ecological adaptability, resource utilization, and biological characteristics under certain environmental conditions (Yuan et al, 2021). Compared with the population distribution in the current period, the D value of the population distribution in the future period is greater than 0.6; the degree of niche overlap is large; the adaptability to habitat resources is similar, and the resource competition is fierce, so there is no significant niche differentiation.…”
Section: Ecological Characteristics Of Distribution Areasmentioning
confidence: 99%